Pengaruh Model Pembelajaran Kooperatif Tipe STAD terhadap Kemampuan Membaca Al-Qur’an Siswa di SMP Ar-Rahmah Samarinda - Amrina Rosyada; Etty Nurbayani; Hajriana Hajriana (Borneo Journal of Islamic Education, 2026)
This study was prompted by the varying levels of students’ comprehension of Qur'anic recitation ability. More proficient students often experienced boredom due to repetitive instructional materials, while less proficient students encountered difficulties in following the lessons. To address this issue, teachers implemented the Student Teams Achievement Divisions (STAD) cooperative learning model. This study aimed to examine the extent of the relationship between the implementation of the STAD learning model and students’ Qur'anic recitation ability according to the rules of tajwid. A quantitative correlational approach was employed. Data were gathered through questionnaires, tests, and documentation. Instrument validity and reliability were established through validity and reliability testing. Data were analyzed using normality and linearity tests, Pearson’s product-moment correlation, coefficient of determination analysis, and the t-test. The findings revealed a correlation coefficient (r) of 0.756, indicating a strong relationship. The coefficient of determination showed that the STAD learning model contributed 75.5% to the variance in students’ Qur’anic recitation ability. Furthermore, the t-test results demonstrated that t-value (6.106) exceeded the critical t-value (1.70113), with a significance level of 0.000 (< 0.05). These findings indicate that the STAD cooperative learning model has a strong and statistically significant influence on students’ ability to recite the Qur’an in accordance with tajwid rules. The study offers concrete evidence demonstrating the efficacy of the STAD learning model in enhancing Qur’anic recitation skills among students with diverse levels of learning ability.